Fractal nature of hard carbon prepared from C60 fullerene. (November 2017) - Starešinić, Damir; Dominko, Damir; Rakić, Iva Šrut; Milat, Ognjen; Ristić, Davor; Ivanda, Mile; Radić, Tea Mišić; Clément, André; Saint-Paul, Michel; Kozlov, Mikhail E.; Biljaković, Katica
Abstract: Hard form of carbon obtained by collapsing C60 fullerene molecules at moderate pressure and temperature was investigated using different imaging techniques at spatial resolutions ranging from angstrom to millimeter. Hierarchical granular morphology has been observed from the atomic up to the sample size length scale, revealing scale independent grain size distribution. The unusual fractal-like structure correlates with unique transport and calorimetric properties of this material. Hard carbon can be considered as a bridge between porous and dense amorphous materials. Graphical abstract: